Uncommon concurrent pulmonary infections: Aspergillus fumigatus and Lomentospora prolificans in an Anti-MDA5 antibody-positive dermatomyositis patient - Maaya Fukumura; Ryosuke Hiwa; Satomi Yukawa; Yasuhiro Tsuchido; Hajime Yoshifuji; Akio Morinobu (Medical Mycology Case Reports)
A 59-year-old female with anti-MDA5 antibody-positive dermatomyositis was treated with prednisolone, tacrolimus, cyclophosphamide, tofacitinib, and plasma exchange. Five months post-treatment, elevated β-D-glucan levels and a pulmonary shadow on CT were noted. Aspergillus fumigatus was identified, leading to voriconazole initiation. A new pulmonary cavity lesion later revealed Lomentospora prolificans. Considering voriconazole resistance, terbinafine was added, resulting in clinical improvement. Vigilant infection monitoring is crucial during anti-MDA5 antibody-positive dermatomyositis treatment.